2017
DOI: 10.4314/jasem.v21i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Elucidation of 15-Acetylguanacone from Soursop (<i>Annona muricata</i> Linn) Fruit and Molecular Docking Experiments

Abstract: Annona muricata (Soursop) has attracted attention due to its content of annonaceous acetogenins, a large family of naturally occurring polyketides isolated from various species of the genus Annonaceae. The ethyl acetate fraction of Annona muricata was subjected to standard isolation protocol-gradient and isocratic silica gel column chromatography-to obtain three waxy and whitish amorphous compounds, 002/A1, 002/A2 and 002/C. The structure of compound 200/A2 was elucidated using 1 H-NMR spectroscopy, infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Their hypoglycemic activity, along with their products, has been assessed and studied in animal trials as well as in humans. Recent studies have shown that the hypoglycemic effects of medicinal plants help in controlling the postprandial rise in blood glucose effectively by inhibiting the carbohydrate hydrolyzing enzymes, such as pancreatic α‐amylase and α‐glucosidase (Agu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their hypoglycemic activity, along with their products, has been assessed and studied in animal trials as well as in humans. Recent studies have shown that the hypoglycemic effects of medicinal plants help in controlling the postprandial rise in blood glucose effectively by inhibiting the carbohydrate hydrolyzing enzymes, such as pancreatic α‐amylase and α‐glucosidase (Agu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%